Design of microstrip patch antenna for IEEE 802.16-2004 applications - Al-Rawachy, Ehab Esam Dawood (2011)
This thesis presents microstrip patch antenna IEEE 802.16-2004 standards for microwave applications and WiMax. Narrow bandwidth (BW) is the main defect of microstrip patch antenna in wireless communication. The bandwidth can be improved by increasing the substrate thickness, and using air as substrate with low dielectric constant. The antennas were fabricated using FR4 board. Two types of microstrip antenna were used, the first was a single microstrip patch antenna and the second was using an air-gap technique as the dielectric between two antenna boards. The spacer of the air-gap has thickness of 2mm. It was made of wood to separate between the two boards. The transmission line model was used to get the approximate dimension for the design. Different parameters were obtained depending on the simulation and measurement. The Computer Simulations Technology (CST) software was used to simulate the design and the measurement was executed by Vector Network Analyzer (VNA). The two designs were compared to each other and found that some improvements were obtained on the air-gap technique. The bandwidth was improved by 4.51 % with air-gap technique and only 1.02 % with the single patch antenna.